Saint-Saëns, Debussy, and Superseding German Musical Taste in the United States - Briscoe, James; Huvet, Chloé (Les Cahiers de la Société québécoise de recherche en musique)

(untitled) (Société québécoise de recherche en musique, 2015)
In an interview published in the October 21, 1908, issue of the Boston Transcript, Debussy had been asked to comment on American musical life. He remarked, “The distinction of a country like [the United States] is that it imbibes from all sources... it is less German bound than are the countries who hear little or no other music through chauvinism or antipathies.” This paper examines the roles of Camille Saint-Saëns (1835-1921) and Claude Debussy (1862-1918) in driving such a modernist evolution. Saint- Saëns performed with and conducted the New York Symphony in 1906, including his symphonic poem Le rouet d’Omphale and playing solo piano in his Africa, Fantaisie pour piano et orchestre. He thereafter appeared in both Chicago and San Francisco, and critics could already hear the modernist aesthetic in formation. When conductor Frederick Stock, a stalwart champion of French music, led Prélude à “L’après- midi-d’un faune” in Chicago in December 1908, the symbolist dimensions of the new music were grasped by both critics and audiences, and Paul Rosenfeld wrote: “We should look to France for the latest gospel [of the new musical advancement] […] Claude Debussy has broken through the limitation of the old, and shall we say he has found new musical dimensions?” Contemporaneously, the premiere of Pelléas et Mélisande in New York dramatically impressed the new hearing on American audiences. To be sure, anti-German feelings after 1910, brought with the Great War, promoted such a shift from the aesthetics of the Gilded Age, but the new French music had itself led the way since just after 1900. By 1923, Carl Van Vechten, in Music after the Great War, wrote, “It is not from the German countries that the musical invention of the past two decades has come. It is from France.”